The Effect of Special Exercises Using with Assisting Aids According to Differentiated Learning (Visual Learners) in Learning Crescent Kick in Fighters of Specialized Taekwondo schools - Al-frejawi, Ahmed; Adnan , Ban (Journal of Physical Education, 2023)
The research aimed at designing aids for learning crescent kick in 12 – 14 years old fighters in specialized schools as well as designing exercises according to differentiated learning (visual learners) in learning crescent kick in the subjects understudy. The researchers used the experimental method on (70) fighters in taekwondo specialized schools. They tested crescent kick skill then the subjects were divided into controlling group (8) fighters and experimental (10) fighters according to learning style scale. The data was collected and treated using proper statistical operations to conclude that individual differences became less among fighters using differentiated learning as well as the aids have a positive effect on learning. Finally, the researchers recommended using the designed aids for teaching and learning taekwondo skills as well as using differentiated learning style and training coaches this strategy so as to make it easier for them to teach it.